2003
DOI: 10.17221/3715-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genotype and Explant Type on Shoot Regeneration in Tomato (Lycopersicon esculentum Mill.) in vitro

Abstract: Abstract:The regeneration capacity of six types of explants (segments from hypocotyl, cotyledons, epicotyl, leaf, internodes and petiole) was compared in 13 cultivars of tomato (Lycopersicon esculentum Mill). Explants were cultured on a regeneration medium containing 1 mg/l zeatin and 0.1 mg/l indole-3-acetic acid. The number of shoot primordia and shoots with 1 or more fully developed leaves was evaluated after 6 weeks. The regeneration capacity was significantly influenced by cultivars and explant types. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 16 publications
4
41
1
1
Order By: Relevance
“…It was observed that BAP had positive effect towards multiple shoot regeneration, a result in agreement with that of the findings of Oktem et al (1999), Fariduddin et al (2004) and Sarker et al (2009). Addition of IAA was found to increase regeneration efficiency as reported earlier by Frary and Earle (1996), Gubis et al (2003) and Cortina and Culianez-Macia (2004).…”
Section: Discussionsupporting
confidence: 91%
“…It was observed that BAP had positive effect towards multiple shoot regeneration, a result in agreement with that of the findings of Oktem et al (1999), Fariduddin et al (2004) and Sarker et al (2009). Addition of IAA was found to increase regeneration efficiency as reported earlier by Frary and Earle (1996), Gubis et al (2003) and Cortina and Culianez-Macia (2004).…”
Section: Discussionsupporting
confidence: 91%
“…The frequency and response of in vitro shoot regeneration differed depending on the type of explants and both the type and concentration of growth regulators added to the regeneration medium (Gubiš et al 2003;Ishag et al 2009). Likewise, shoot bud induction from both CN and nodal explants was observed in all treatments containing TDZ though with varied frequencies.…”
Section: Effect Of Thidiazuronmentioning
confidence: 99%
“…Both we and MOGHAIEB et al (1999) Concluding remarks. This study confirmed our previous results that combining ZEA and IAA in the tissue culture medium had favourable effects on shoot organogenesis in tomato hypocotyl and cotyledon explants (GUBIŠ et al 2003). The transfer of hypocotyl explants onto a medium with half concentration of ZEA and IAA showed positive effects on shoot organogenesis.…”
supporting
confidence: 91%